Complex Systems Design & Management Proceedings of the Sixth International Conference on Complex Systems Design & Management, CSD&M 2015 - Auvray, Gérard; Bocquet, Jean-Claude.; Bonjour, Eric.; Krob, Daniel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book contains all refereed papers that were accepted to the sixth edition of the « Complex Systems Design & Management Paris » (CSD&M Paris 2015) international conference which took place in Paris (France) on November 23-25, 2015. These proceedings cover the most recent trends in the emerging field of complex systems sciences & practices from an industrial and academic perspective, including the main industrial domains (aeronautics & aerospace, defense & security, electronics & robotics, energy & environment, health & welfare, software & e-services, transportation), scientific & technical topics (systems fundamentals, systems architecture & engineering, systems metrics & quality, systems modeling tools) and systems types (artificial ecosystems, embedded systems, software & information systems, systems of systems, transportation systems). The CSD&M Paris 2015 conference is organized under the guidance of the CESAMES non-profit organization, address: CESAMES, 8 rue de Hanovre, 75002 Paris, France.
Keywords: Dynamics; Nonlinear theories; Technological innovations; Control engineering; Robotics; Automation; System theory; Mathematical physics; Applied Dynamical Systems; Innovation and Technology Management; Control, Robotics, Automation; Complex Systems; Theoretical, Mathematical and Computational Physics